(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2022)
Banking Sector plays an important role in the growth and development of Indian economy ineach and every aspect.The main aim of the study is to compare and evaluate the financial performanceof selected banks using CAMEL rating system. The research is descriptive and analytical in nature . Thedata used for study was entirely secondary in nature and was taken from the annual reports of thebanks, Bulletins, Periodicals, News letters, Internal reports of the bank, Journals, Magazines andWebsites. The collected data has been analysed CAMEL framework.The banks selected for analysis areICICI Bank, HDFC Bank, YES Bank, AXIS Bsnk and FEDERAL Bank..The period of study for the selectedbanks from 2014 to 2018 period.The study found that HDFC Bank and AXIS Bank are the best banks.